Translocation of Macaca fascicularis to the Sungkai and Sg. Dusun wildlife reserve - Azmi Johor (2022)
Translocation is not the best solution to a threatened population in an area. This is because the new environment will create a number of problems for the animals. A number of factors has to be taken into consideration to ensure the survival of the species. Such factors include a suitable habitat, food source, predator-prey factor and inter and intra-specific competition. For the study. two groups of M. fascicularis (n₁ = n2 =20) were marked and released in two Wildlife Reserve to evaluate the success of the two groups in the wild.